USING NARRATIVE TEXT TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT SENIOR HIGH SCHOOL - Rahmatia Sofyan; Hasnani; Cayati (STKIP Subang, 2025)
Rahmatia Sofyan, 2025, “Using Narrative Text in Improving the Students’Vocabulary Mastery At Senior High School.” Supervised by Hasnani and Cayati.This study aims to determine the effect of using narrative text on the vocabularyskills of tenth-grade students at SMA Negeri 19 Makassar in the 2024/2025academic year. This study used a pre-experimental method with a quantitativeapproach. The population of this study was 30 students. This study used a pre-testand post-test, followed by four sessions of treatment using narrative text. The datafor this study were obtained through pre-tests and post-tests, where the researchertook students’ vocabulary scores. The results showed that the average pre-testscore was 76.7667, while the average post-test score was 87.7667. There was asignificant difference from the average score in the experimental class. The scoreincreased by 11.7 after treatment with a significance level of 0.000 < 0.05; therefore,H0 is rejected and H1 is accepted. Based on the results of this study, it can beconcluded that there was an increase in students’ vocabulary through the use ofnarrative text in grade X 3 students of SMA Negeri 19 Makassar.